Implementation of Papua Nature Exploration (PNE) in Scout Extracurricular Activities to Build Students’Responsible and Nature-Loving Character at Elementary School - Didit Shela Nurfatul Daniar; Iis Siti Aisyah; Lud Waluyo (JIP Jurnal Ilmiah PGMI, 2025)
Papua Nature Exploration (PNE) is an extracurricular Scout activity at Muhammadiyah Teminabuan Elementary School, South Sorong. This activity aims to shape students' character of responsibility and love for nature. This study aims to examine the implementation, supporting and inhibiting factors, and how to deal with obstacles in PNE activities. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The collected data were analyzed using qualitative analysis techniques, including data reduction, data display, and conclusion drawing. Data triangulation was applied to ensure validity by cross-checking information obtained from different sources. The results showed that Papua Nature Exploration (PNE) is a structured scouting extracurricular activity that fosters responsibility and love for nature through team formation, environmental education, outdoor survival training, exploration, conservation efforts, and interactive games. PNE activities were effective in building character of responsibility and love for nature in grades V and VI students. This is reflected in the attitude of caring, focusing, and protecting the environment during the activity. Supporting factors for the success of PNE include the involvement of Scout Leaders, Muhammadiyah Middle School students, PDM Sorong Selatan, and student enthusiasm. Obstacles found include the distance of the activity location which is far from the school and unpredictable weather. This study recommends the development of interesting activities to instill positive character in students. In addition, it is recommended to further develop PNE activities using experimental methods to test their effectiveness on a larger scale.